The Intertwined Influence of Environmental and Organizational Factors on Corporate Wellness in the IT Sector: A Comprehensive Study - * Rakesh Thampi S, **Dr. B. Pohutezhini (South Eastern European Journal of Public Health, 2025)
The IT sector's rapid growth and expansion have placed immense pressure on its workforce, leading to increased demands on employees (Ayyagari, 2011). This has resulted in a rise in work-related stress, burnout, and a range of health issues, including cardiovascular problems, musculoskeletal disorders, and mental health conditions (Tarafdar et al., 2011). Consequently, the development and implementation of effective corporate wellness programs have become crucial for safeguarding employee well-being and bolstering organizational performance. The concept of corporate wellness has garnered increasing attention, particularly within the IT sector, which is often characterized by high-stress levels, long working hours, and prevalent sedentary behavior (Katz & Krueger, 2013). All of these factors can contribute to a range of physical and mental health problems, thereby underscoring the critical need for effective corporate wellness initiatives. This is further compounded by the rapidly evolving nature of the IT landscape and its associated pressures. Therefore, a proactive approach to employee well-being is not only ethically sound but also strategically advantageous for IT organizations.